2001
DOI: 10.1002/dvdy.1220
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nodal signaling targets by array analysis of induced complex probes

Abstract: Nodal signaling controls germ layer formation, left-right asymmetry, and patterning of the brain in the vertebrate embryo. Cellular responses to Nodal signals are complex and include changes in gene expression, cell morphology, and migratory behavior. Only little is known about the genes regulated by Nodal signaling. We designed a subtractive screening strategy by using a constitutively active Nodal receptor to identify putative target genes of Nodal signals in the early gastrula of zebrafish embryos. By quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…The Fgf signalling pathway is a relay in the induction of oep by the Tar*/Nodal pathway It was shown that the Nodal pathway might be regulated through positive and negative feedback (Meno et al, 1999;Thisse and Thisse, 1999;Hyde and Old, 2000;Dickmeis et al, 2001). To further elucidate the genetic interactions and cellular mechanisms involved, we examined the cell-autonomous and cell-nonautonomous induction of Nodal pathway components in cells with constitutively active intracellular Activin/Nodal signalling.…”
Section: Resultsmentioning
confidence: 99%
“…The Fgf signalling pathway is a relay in the induction of oep by the Tar*/Nodal pathway It was shown that the Nodal pathway might be regulated through positive and negative feedback (Meno et al, 1999;Thisse and Thisse, 1999;Hyde and Old, 2000;Dickmeis et al, 2001). To further elucidate the genetic interactions and cellular mechanisms involved, we examined the cell-autonomous and cell-nonautonomous induction of Nodal pathway components in cells with constitutively active intracellular Activin/Nodal signalling.…”
Section: Resultsmentioning
confidence: 99%
“…Each of these studies yielded important and complementary data, but it is useful to perform a detailed comparison to assess the endogenous approach. Our method was best for identifying non-Nodal mesendoderm pathway members (i.e., FGF, WNT, and retinoic acid), with 12 of our top 60 genes being in these categories, compared with 9 of 98 (28) and 6 of 75 (27) in the other studies that presented their nonvalidated hits (Table S2). Our approach was also successful for identifying Nodal pathway genes.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our microarray analysis is the first such study on endogenous germ layer precursors in zebrafish; however, three papers have reported on the transcriptomes of zebrafish embryos forced to over-or underproduce mesendoderm via alterations in Nodal signaling (27)(28)(29). Each of these studies yielded important and complementary data, but it is useful to perform a detailed comparison to assess the endogenous approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic analyses in zebrafish indicate that FoxH1 and Mixer do not fully account for Nodal-mediated transcriptional events (Kunwar et al, 2003), indicating that additional transcription factors involved in Nodal responses remain to be identified. At present, most known targets of the Nodal pathway, such as Nodal, Lefty2, Pitx2, FoxA2 and Lhx1 (Table 1), undergo transcriptional activation in response to Nodal signals, whereas a few are transcriptionally repressed (Dickmeis et al, 2001;Whitman, 2001). Nodal itself is positively autoregulated through the asymmetric enhancer (ASE) located in its first intron (Adachi et al, 1999;Norris et al, 2002;Norris and Robertson, 1999), and by an upstream left-side specific enhancer (LSE) (Saijoh et al, 2005;Vincent et al, 2004).…”
Section: Signal Transducers and Transcriptional Regulatorsmentioning
confidence: 99%